Effect of inductance on the parameters of the plasma focus in a pulsed coaxial accelerator - Useinov B.М.; Solodovnik, A.A.; Zhumabayeva, S.K. (Recent Contributions to Physics, 2021)
Based on the physical analysis of the processes occurring in pulsed plasma accelerators, the possibility of their use for the creation and study of a plasma focus is justified. In particular, the influence of inductance on the parameters of the plasma focus in kilojoule-range «Plasma focus» (PF) installations created on the basis of a pulsed coaxial accelerator is studied. An equivalent installation scheme is proposed and justified, based on the analysis of which the influence of the inductance of the circuit and the capacitance of the capacitor bank on the value of the maximum current and neutron output is analyzed, without taking into account the parameters of the spark gap and the conducting wires. Based on the theoretical estimate of the inductance of the installation, its most probable value is calculated. . It turned out that in the installations of the considered energy range, the inductance is approximately 7.5•10-7 Gn and depends on the capacitance of the capacitor bank. On the contrary, in installations with megajoule energy, the inductance does not depend on the number and capacity of capacitors, so that an increase in the latter does not affect the increase in current strength. Experimental and theoretical dependences of the discharge current on the applied voltage at different capacitances of the capacitor bank are obtained. A comparative analysis of theoretical and experimental current waveforms is presented. The greatest coincidence of theoretical and experimental results was found for the duration of the discharge pulse T = 30 microseconds.